2001
DOI: 10.1002/1527-2648(200109)3:9<717::aid-adem717>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of a Porous PMMA Filter Material by Nanodispersed Clay

Abstract: A multi-scale, multi-level modeling approach was presented for a woven-fabric composite, especially for a plain weave composite, even though the approach could be generalized to different weaves of woven-fabric composites. The technique can simulate progressive failure in woven-fabric composites to predict residual stiffness and strength along with the progressive failure. Some examples were presented using the technique to calculate the effective stiffness or strength at the constituent material level like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The results in table (1) shown that the impact strength of the samples immersed in (HCL, KOH) decreased after immersion due to the effect of (HCL, KOH) in breaking the hydrogen bond between polymer chains and interfacial bonds in the interface between fibers and epoxy resin, therefore the composite become more brittle than before immersion. While we notice that the impact strength of the samples immersed in (distilled water, Benzene, Kerosene) increased after immersion because of the hydroxide groups in those solutions making the composite more ductile and can absorb more energy before fracture [12].…”
Section: Effect Of Chemical Solutions On Mechanical Properties Of Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results in table (1) shown that the impact strength of the samples immersed in (HCL, KOH) decreased after immersion due to the effect of (HCL, KOH) in breaking the hydrogen bond between polymer chains and interfacial bonds in the interface between fibers and epoxy resin, therefore the composite become more brittle than before immersion. While we notice that the impact strength of the samples immersed in (distilled water, Benzene, Kerosene) increased after immersion because of the hydroxide groups in those solutions making the composite more ductile and can absorb more energy before fracture [12].…”
Section: Effect Of Chemical Solutions On Mechanical Properties Of Com...mentioning
confidence: 99%
“…Composite materials are materials which are made by artificially combining two or more components, thus interface are present in a composite material [1].Many composites used today are at the leading edge of materials technology with performance and costs appropriate to ultra demanding applications such as spacecraft. But materials combining the best aspects of dissimilar constituents have been used by nature for million of years [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a widely applied engineering material, polymethyl methacrylate (PMMA) has many excellent properties such as good weathering resistance, high surface hardness, and strength, especially the transparency and durability . However, PMMA often exhibits brittle fracture behaviors at room temperature, which may bring disastrous consequence for the structural application. In order to design the structural components with safety and to prevent the brittle fracture, it is very crucial to well understand the fracture mechanism of PMMA.…”
Section: Introductionmentioning
confidence: 99%